Pyricularia sp. jiangsuensis, a new cryptic rice panicle blast pathogen from rice fields in Jiangsu Province, China - Du, Yan; Qi, Zhongqiang; Liang, Dong; Yu, Junjie; Yu, Mina; Zhang, Rongsheng; Cao, Huijuan; Yong, Mingli; Pan, Xiayan; Yin, Xiaole; Qiao, Junqing; Liu, Youzhou; et al. (Wiley, 2021)
Pyricularia oryzae is a multi‐host pathogen causing cereal disease, including the devastating rice blast. Panicle blast is a serious stage, leading to severe yield loss. Thirty‐one isolates (average 4.1%) were collected from the rice panicle lesions at nine locations covering Jiangsu province from 2010 to 2017. These isolates were characterized as Pyricularia sp. jiangsuensis distinct from known Pyricularia species. The representative strain 18‐2 can infect rice panicle, root and five kinds of grasses. Intriguingly, strain 18‐2 can co‐infect rice leaf with P. oryzae Guy11. The whole genome of P. sp. jiangsuensis 18‐2 was sequenced. Nine effectors were distributed in translocation or inversion region, which may link to the rapid evolution of effectors. Twenty‐one homologues of known blast‐effectors were identified in strain 18‐2, seven effectors including the homologues of SLP1, BAS2, BAS113, CDIP2/3, MoHEG16 and Avr‐Pi54, were upregulated in the sample of inoculated panicle with strain 18‐2 at 24 hpi compared with inoculation at 8 hpi. Our results provide evidences that P. sp. jiangsuensis represents an addition to the mycobiota of blast disease. This study advances our understanding of the pathogenicity of P. sp. jiangsuensis to hosts, which sheds new light on the adaptability in the co‐evolution of pathogen and host.